2018
DOI: 10.3389/fphar.2018.00525
|View full text |Cite
|
Sign up to set email alerts
|

The Active Components of Fuzheng Huayu Formula and Their Potential Mechanism of Action in Inhibiting the Hepatic Stellate Cells Viability – A Network Pharmacology and Transcriptomics Approach

Abstract: Purpose: This study aimed to identify the active components of Fuzheng Huayu (FZHY) formula and the mechanism by which they inhibit the viability of hepatic stellate cells (HSCs) by a combination of network pharmacology and transcriptomics.Methods: The active components of FZHY formula were screened out by text mining. Similarity match and molecular docking were used to predict the target proteins of these compounds. We then searched the STRING database to analyze the key enriched processes, pathways and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…Recently, integrated strategies based on bioinformatics, system biology, and high-throughput analytical techniques have emerged as a holistic and efficient tool to solve this issue (Ning et al, 2018; Xing et al, 2018; Huang et al, 2019). Network pharmacology gives us helpful tools to screen potential bioactive ingredients and understand the molecular mechanisms underlying the therapeutic effects by constructing component–target and target–disease networks (Li and Zhang, 2013; Yuan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, integrated strategies based on bioinformatics, system biology, and high-throughput analytical techniques have emerged as a holistic and efficient tool to solve this issue (Ning et al, 2018; Xing et al, 2018; Huang et al, 2019). Network pharmacology gives us helpful tools to screen potential bioactive ingredients and understand the molecular mechanisms underlying the therapeutic effects by constructing component–target and target–disease networks (Li and Zhang, 2013; Yuan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The content of major ingredients was measured on-site during the manufacturing processes, and as a quality inspection standard; as such, the procedures can be fully reproducible. 7 The fact that the active components of FZHY formula and their potential mechanism in inhibiting hepatic stellate cells' viability have been identified using network pharmacology and transcriptomics 24 has provided the evidence underlying its known antifibrotic action.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced liver cirrhosis is still incurable and can lead to liver failure and death [20]. Although the molecular mechanisms of FZHY in HPC protection and its antifibrotic effects are not fully clear, many reports have shown its antifibrotic effects without adverse effects [9,21,22]. Thus, evaluating the antifibrotic and HPC-protecting effects of FZHY and clarifying its mechanisms of action is important.…”
Section: Discussionmentioning
confidence: 99%
“…Major compounds and targets were selected using topological parameters and a structure herb-compound-target-signaling pathway network of FZHY, which resulted in the selection of 6 compounds, 39 potential targets and 12 pathways. Previous studies have reported that the selected major compounds, such as kaempferol and tanshinone IIA, inhibit the proliferation of HSCs [21], luteolin has hepatoprotective activity through the regulation of SREBP-1c phosphorylation and AMP-activated protein kinase [27], beta-sitosterol prevents hepatotoxicity [28], and hederagenin can attenuate non-alcoholic hepatic steatosis [29].…”
Section: Discussionmentioning
confidence: 99%